An Antivirulence Approach for Preventing Cryptococcus neoformans from Crossing the Blood-Brain Barrier via Novel Natural Product Inhibitors of a Fungal Metalloprotease - Phylicia A. Aaron (American Society for Microbiology, 2020)
ABSTRACT Cryptococcus neoformans (Cn) is the leading cause of fungal meningitis, a deadly disease with limited therapeutic options. Dissemination to the central nervous system hinges on the ability of Cn to breach the blood-brain barrier (BBB) and is considered an attribute of Cn virulence. Targeting virulence instead of growth for antifungal drug development has not been fully exploited despite the benefits of this approach. Mpr1 is a secreted fungal metalloprotease not required for fungal growth, but rather, it functions as a virulence factor by facilitating Cn migration across the BBB. This central role for Mpr1, its extracellular location, and lack of expression in mammalian cells make Mpr1 a high-value target for an antivirulence approach aimed at developing therapeutics for cryptococcal meningitis. To test this notion, we devised a large-scale screen to identify compounds that prohibited Cn from crossing the BBB by selectively blocking Mpr1 proteolytic activity, without inhibiting the growth of Cn. A phytochemical natural product-derived library was screened to identify new molecular scaffolds of prototypes unique to a Cn microecosystem. Of the 240 pure natural products examined, 3 lead compounds, abietic acid, diosgenin, and lupinine inhibited Mpr1 proteolytic activity with 50% inhibitory concentration (IC50) values of <10 μM, displayed little to no mammalian cell toxicity, and did not affect Cn growth. Notably, the lead compounds blocked Cn from crossing the BBB, without damaging the barrier integrity, suggesting the bioactive molecules had no off-target effects. We propose that these new drug scaffolds are promising candidates for the development of antivirulence therapy against cryptococcal meningitis. IMPORTANCE Fungal infections like cryptococcal meningitis are difficult to resolve because of the limited therapies available. The small arsenal of antifungal drugs reflect the difficulty in finding available targets in fungi because like mammalian cells, fungi are eukaryotes. The limited efficacy, toxicity, and rising resistance of antifungals contribute to the high morbidity and mortality of fungal infections and further underscore the dire but unmet need for new antifungal drugs. The traditional approach in antifungal drug development has been to target fungal growth, but an attractive alternative is to target mechanisms of pathogenesis. An important attribute of Cryptococcus neoformans (Cn) pathogenesis is its ability to enter the central nervous system. Here, we describe a large-scale screen that identified three natural products that prevented Cn from crossing the blood-brain barrier by inhibiting the virulence factor Mpr1 without affecting the growth of Cn. We propose that compounds identified here could be further developed as antivirulence therapy that would be administered preemptively or serve as a prophylactic in patients at high risk for developing cryptococcal meningitis.